Six simple steps towards making GEES fieldwork more accessible and inclusive. - Lawrence, Anya; Dowey, Natasha (Area (0004-0894), 2022)
Fieldwork is a defining aspect of Physical Geography, Earth and Environmental Science (GEES) programme curricula. At its best, fieldwork offers students valuable opportunities to develop independent research skills in real‐world situations, examine analogues for a range of scientific concepts, and socialise with peers. It offers experiences that are challenging to replicate using virtual/remote learning. However, at its worst, traditional fieldwork practice and culture can present barriers to access and hostile environments that epitomise the broader equity, diversity, and inclusivity problems faced by GEES disciplines. With the role of fieldwork increasingly being called into question, here we promote simple adaptations that can make fieldwork more accessible and enjoyable for all.